Direct microwave-assisted amino acid synthesis by reaction of succinic acid and ammonia in the presence of magnetite. Issue 4 (19th June 2013) - Jiang, Nan; Liu, Dandan; Shi, Weiguang; Hua, Yingjie; Wang, Chongtai; Liu, Xiaoyang
Abstract: Since the discovery of submarine hot vents in the late 1970s, it has been postulated that submarine hydrothermal environments would be suitable for emergence of life on Earth. To simulate warm spring conditions, we designed a series of microwave-assisted amino acid synthesis involving direct reactions between succinic acid and ammonia in the presence of the magnetite catalyst. These reactions which generated aspartic acid and glycine were carried out under mild temperatures and pressures (90–180 °C, 4–19 bar). We studied this specific reaction inasmuch as succinic acid and ammonia were traditionally identified as prebiotic compounds in primitive deep-sea hydrothermal systems on Earth. The experimental results were discussed in both biochemical and geochemical context to offer a possible route for abiotic amino acid synthesis. With extremely diluted starting materials (0.002 M carboxylic acid and 0.002 M ammonia) and catalyst loading, an obvious temperature dependency was observed in both cases [neither product was detected at 90 °C in comparison with 21.08 μmol L −1 (aspartic acid) and 70.25 umol L −1 (glycine) in 180 °C]. However, an opposite trend presented for reaction time factor, namely a positive correlation for glycine, but a negative one for aspartic acid.